Effect of Bazi Bushen Capsule on D‐Galactose‐Induced Human Endothelial Cell Senescence Through PI3K/Akt/eNOS Signaling Pathway - Lulu Yao; Fuyao Li; Jingnian Ni; Mingqing Wei; Ting Li; Jing Shi; Jinzhou Tian (Aging Medicine)
ABSTRACT Objectives BaZi BuShen capsule (BZBS) is a Chinese herbal prescription with the function of nourishing the kidney, replenishing essence, and combating aging. This study aims to investigate the effects of BZBS on aging endothelial cells and to elucidate the underlying mechanisms. Methods An aging human brain microvascular endothelial cells (HBMECs) model was established using D‐galactose (D‐gal) for 24 h. The efficacy of the model was evaluated by the positive rate of senescence‐associated β‐galactosidase (SA‐β‐Gal) staining. The treatment was administered using drug‐containing serum of BZBS. The experimental groups comprised the following: Control, Model, and groups treated with drug‐containing serum at low (BZBSL), medium (BZBSM), and high (BZBSH) doses of BZBS, in addition to a pathway inhibitor group (LY294002 [5 μM/L]). Western blotting and immunofluorescence assays were conducted to evaluate the expression levels of proteins. Nitric oxide (NO) levels in the cells were detected using an Assay Kit. The experiments were independently repeated five times. Results D‐gal significantly elevated the SA‐β‐Gal positive rate in HBMECs. Intervention with BZBS significantly reduced the percentage of SA‐β‐Gal positive cells (p < 0.001). Compared to the Model group, drug‐containing serum of BZBS significantly increased the expression levels of PI3K, p‐Akt, Akt, and eNOS (p < 0.010) and elevated NO levels in the cells (p < 0.010), by which BZBS ameliorated HBMECs aging and enhanced the function of aging HBMECs. Conclusions Our findings indicate that BZBS can mitigate D‐gal‐induced aging in HBMECs by activating the PI3K/Akt/eNOS signaling pathway.